The Impact of Customers’ Trust and Satisfaction on Interest in Buying Clothes Online on Shopee at SMA Swasta Bina Guna Tanah Jawa - Romatua Hutapea; Binsar Tison Gultom; Benjamin Albert Simamora (International Journal of Integrated Science and Technology, 2023)
The problem in this research is the low interest in buying clothing products online at Shopee at Bina Guna Tanah Java Private High School. This research aims to determine consumer trust and online consumer satisfaction with Shopee at Bina Guna Tanah Jawa Private High School. This type of research is quantitative research with a quantitative descriptive data analysis approach. The research population was students at the Bina Guna Tanah Java Private High School with a total of 202 students. The research sample consisted of 120 students. The sampling technique used was random sampling by the researcher according to the class at school. The data collection technique used was a questionnaire. The hypothesis making technique uses multiple regression analysis and the coefficient of determination (R2). The research results show that: 1) there is a positive and significant influence of consumer trust on buying interest. This can be seen in the t test where the calculated t value of consumer trust (4.440) > t table value (1.65787) which means this variable is significant. 2) there is a positive and significant influence of consumer satisfaction on the positive influence of buying interest. This is found in the t test where the calculated t value of consumer satisfaction is (3.123) > the table value (1.65787) which means that this variable is significant. 3) consumer trust and consumer satisfaction together influence buying interest. This can be seen in the F test where the calculated F value (12.256) > table F value (3.07). The R square coefficient of determination test was found to be 0.173, which means that 17.3% of the variables of consumer trust and consumer satisfaction influence the interest in buying clothing products online at Shopee at Bina Guna Tanah Jawa Private High School and the remaining 82.7% is the influence of other variables. not examined in this study.